Biomechanical responses of peripheral nerves in human, pig and rat: a comparative study - Singh, Anita; Kozin, Scott; Balasubramanian, Sriram (Frontiers in Bioengineering and Biotechnology, 2025)
Peripheral nerve injury primarily results from trauma and understanding their mechanical responses is critical to both, the prevention, and the management of sustained injuries. This study aimed to determine and compare the biomechanical responses of sural nerve in human infants, and age-equivalent pig and rat animal models. Biomechanical failure tensile testing was performed on freshly harvested sural nerves. Obtained failure load, and calculated failure stress, corresponding strain, and Young’s Modulus (E) were compared among various species. Histological analysis was also performed on tested nerves to determine the extent of vascular and fiber damage. No significant differences in the failure properties of the age-equivalent human and pig sural nerves were observed. However, the failure load and E values were significantly higher in human and pig nerves when compared to rat nerves. Failure stress was significantly higher in humans than in rat nerves. Histological analysis reported non-significant species-specific differences. In summary, rat sural nerves reported significantly weaker biomechanical properties while the observed structural damage was similar in the three studied species. Obtained data offers an understanding of species-specific differences in the nerve biomechanical properties and can guide translational research that aims to advance the area of peripheral nerve injury and repair.